Wild Baby Animals - Wallace, Karen; Nang ChanYeema (New York, USA DK Publishing Inc., 2000)
Describes some of the differences in the ways various baby animals--including monkeys, rhinos, wolves, seals, and elephants--behave and grow.
Keywords: Level Books